2014
DOI: 10.1007/s00705-014-2181-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of a Chinese strain of bovine adenovirus type 3 infection in albino guinea pigs

Abstract: Bovine adenovirus type 3 (BAV-3) is considered one of the most important respiratory tract agents of cattle and is widespread among cattle around the world. A BAV-3 strain was isolated from a bovine nasal swab for the first time in China in 2009 and named HLJ0955. Subsequently, BAV-3 has frequently been isolated from calves with respiratory diseases in China. To date, only limited study on the pathogenesis of BAV-3 infection in cotton rats has been conducted, and the pathogenesis of BAV-3 infection in guinea p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
(36 reference statements)
1
5
1
Order By: Relevance
“…The results of viral titers and viral loads were summarized in Supplementary Table S1 and line graphs were constructed based on the data ( Figure 6 ). Unlike previous reports where the virus could only be detected in the lungs and trachea ( 22 , 23 ), in this study it was detected in multiple organs and even in the blood throughout the infection period. With the exception of the trachea and blood, the replication of the virus in all organs showed a certain regularity, reaching the highest viral titers and viral loads on a given day and then gradually decreasing.…”
Section: Resultscontrasting
confidence: 87%
See 3 more Smart Citations
“…The results of viral titers and viral loads were summarized in Supplementary Table S1 and line graphs were constructed based on the data ( Figure 6 ). Unlike previous reports where the virus could only be detected in the lungs and trachea ( 22 , 23 ), in this study it was detected in multiple organs and even in the blood throughout the infection period. With the exception of the trachea and blood, the replication of the virus in all organs showed a certain regularity, reaching the highest viral titers and viral loads on a given day and then gradually decreasing.…”
Section: Resultscontrasting
confidence: 87%
“…Subsequently, the replication kinetics of the virus in various tissues and organs was detected. The results of virus titration and qPCR showed that the virus could be detected as early as 24 h after infection, and maintained high viral loads from 1 to 15 days, with a much longer duration of infection than previously reported for HLJ0955 strain (22,23). In addition, the virus could infect and replicate in various organs, such as heart, liver, spleen, lung, kidney, trachea and even blood, which was different from the previous report that the virus replicated only in the lung and trachea (22)(23)(24), indicating that the virus tissue tropism has been altered and can cause viremia.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Bovine adenoviruses (BAdVs) are involved in the bovine respiratory disease complex and are a cause of significant economic losses in the beef and dairy industries ( 9 , 23 ). The ten known BAdV serotypes are divided into two groups based on viral neutralization tests.…”
Section: Introductionmentioning
confidence: 99%